Violation of Psychological Contract- A Case Study on Gehc Malaysia - Sekhon, Sameeta Kaur (2010)
This research was conducted in GEHC Malaysia to see if there has been a violation of psychological contract during the transformation. I worked in this organisation for 4 years and it has been an enriching experience. The method adopted is qualitative using grounded theory. 10 interviews were conducted and transcribed. 5 themes occurred during the transcription; structure, culture, leadership, motivation and psychological contract. The themes was analysed and discussed. The themes that emerged were supported by theories found in literature review. This research has shows that psychological contract gets violated if an organisation does not get its structure, culture, leadership and motivation correct. If one factor is neglected, all the other factors would be jeopardised as well. This was clearly shown when power is not decentralised; local leader has less authority in decision-making. This brings high dissatisfaction especially when employee feedback is not obtained before changes in workflow. Dissatisfaction leads to low motivation and eventually violation of psychological contract. When this happens, there is high employee turnover, which brings in additional cost to organisations.